2021
DOI: 10.1136/bmjgh-2021-005292
|View full text |Cite
|
Sign up to set email alerts
|

Defining global health: findings from a systematic review and thematic analysis of the literature

Abstract: IntroductionDebate around a common definition of global health has seen extensive scholarly interest within the last two decades; however, consensus around a precise definition remains elusive. The objective of this study was to systematically review definitions of global health in the literature and offer grounded theoretical insights into what might be seen as relevant for establishing a common definition of global health.MethodA systematic review was conducted with qualitative synthesis of findings using pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
33
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 92 publications
0
33
0
3
Order By: Relevance
“…In order to consider the wider impact of medications in various areas (including society and economics), a novel paradigm of drug risk management relating directly to public health is needed. For such purpose, the definition of Global Public Health may be useful: “Global health emphasis transnational health issues, determinants, and solutions; involves many disciplines within and beyond the health sciences and promotes interdisciplinary collaboration; and is a synthesis of population-based prevention with individual-level clinical care.” [ 25 ] Global Public Health needs to encompass medicines risk management strategies and tactics as part of a more inclusive interdisciplinary approach. Tools, such as indicators for assessing the global impact of identified and validated side effects within a more defined parameters (nation, region, etc.)…”
Section: Global Challenges and Opportunitiesmentioning
confidence: 99%
“…In order to consider the wider impact of medications in various areas (including society and economics), a novel paradigm of drug risk management relating directly to public health is needed. For such purpose, the definition of Global Public Health may be useful: “Global health emphasis transnational health issues, determinants, and solutions; involves many disciplines within and beyond the health sciences and promotes interdisciplinary collaboration; and is a synthesis of population-based prevention with individual-level clinical care.” [ 25 ] Global Public Health needs to encompass medicines risk management strategies and tactics as part of a more inclusive interdisciplinary approach. Tools, such as indicators for assessing the global impact of identified and validated side effects within a more defined parameters (nation, region, etc.)…”
Section: Global Challenges and Opportunitiesmentioning
confidence: 99%
“…Terminology describing global health activities has changed and expanded over past decades as our values in this space have changed [ 1 ]. Early on, tropical medicine focused on maintaining a labor force in the colonial tropics.…”
mentioning
confidence: 99%
“…[3][4][5][6] In a recent article published in BMJ Global Health, Salm et al reported a comprehensive systematic review and thematic analysis of the definitions of global health over an 11-year period. 7 They found that most definitions of global health in the articles meeting their inclusion criteria fell within one of the following four main themes: (1) a multiplex approach to worldwide health improvement taught and pursued through research institutions; (2) an ethical initiative that is guided by justice principles; (3) a form of governance that yields national, international, translational and supranational influence through political decision making, problem identification and allocation and exchange of resources across borders and (4) a polysemous concept with historical antecedents and emergent future. 7 Salm et al conclude that 'global health' means many different things, and the definitions are conditioned by who makes them and the purpose and target recipients of its practice or research.…”
mentioning
confidence: 99%
“…7 They found that most definitions of global health in the articles meeting their inclusion criteria fell within one of the following four main themes: (1) a multiplex approach to worldwide health improvement taught and pursued through research institutions; (2) an ethical initiative that is guided by justice principles; (3) a form of governance that yields national, international, translational and supranational influence through political decision making, problem identification and allocation and exchange of resources across borders and (4) a polysemous concept with historical antecedents and emergent future. 7 Salm et al conclude that 'global health' means many different things, and the definitions are conditioned by who makes them and the purpose and target recipients of its practice or research. They propose that global health could be defined as 'an area of research and practice committed to the application of overtly multidisciplinary, multisectoral and culturally sensitive approached for reducing health disparities that transcend national borders'.…”
mentioning
confidence: 99%
See 1 more Smart Citation